RTS, S/AS01E malaria vaccine induces IgA responses against CSP and vaccine-unrelated antigens in African children in the phase 3 trial. Issue 4 (22nd January 2021) - Suau, Roger; Vidal, Marta; Aguilar, Ruth; Ruiz-Olalla, Gemma; Vázquez-Santiago, Miquel; Jairoce, Chenjerai; Nhabomba, Augusto J.; Gyan, Ben; Dosoo, David; Asante, Kwaku Poku; Owusu-Agyei, Seth; Campo, Joseph J.; et al.
Abstract: Background: The evaluation of immune responses to RTS, S/AS01 has traditionally focused on immunoglobulin (Ig) G antibodies that are only moderately associated with protection. The role of other antibody isotypes that could also contribute to vaccine efficacy remains unclear. Here we investigated whether RTS, S/AS01E elicits antigen-specific serum IgA antibodies to the vaccine and other malaria antigens, and we explored their association with protection. Methods: Ninety-five children (age 5–17 months old at first vaccination) from the RTS, S/AS01E phase 3 clinical trial who received 3 doses of RTS, S/AS01E or a comparator vaccine were selected for IgA quantification 1 month post primary immunization. Two sites with different malaria transmission intensities (MTI) and clinical malaria cases and controls, were included. Measurements of IgA against different constructs of the circumsporozoite protein (CSP) vaccine antigen and 16 vaccine-unrelated Plasmodium falciparum antigens were performed using a quantitative suspension array assay. Results: RTS, S vaccination induced a 1.2 to 2-fold increase in levels of serum/plasma IgA antibodies to all CSP constructs, which was not observed upon immunization with a comparator vaccine. The IgA response against 13 out of 16 vaccine-unrelated P. falciparum antigens also increased after vaccination, and levels were higher in recipients of RTS, S than in comparators. IgA levels to malaria antigens before vaccination were more elevated in the high MTI than the low MTI site. No statistically significant association of IgA with protection was found in exploratory analyses. Conclusions: RTS, S/AS01E induces IgA responses in peripheral blood against CSP vaccine antigens and other P. falciparum vaccine-unrelated antigens, similar to what we previously showed for IgG responses. Collectively, data warrant further investigation of the potential contribution of vaccine-induced IgA responses to efficacy and any possible interplay, either synergistic or antagonistic, with protective IgG, as identifying mediators of protection by RTS, S/AS01E immunization is necessary for the design of improved second-generation vaccines. Clinical trial registration : ClinicalTrials.gov: NCT008666191.